The Work-Life Balance Phenomenon Among Teachers: What Role Does Perceived Organizational Support Play? - Faeqotus Soleha, Tiki; Dyan Prastika, Netty (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Work-life balance is the ability to fairly divide roles between work life and personal life. One of the driving factors that can improve work-life balance is the perceived organizational support that makes teachers feel well-being in living their work life. So this perceived is needed to achieve work-life balance. However, in reality there are still teachers who lack the perceived organizational support. The purpose of this study was to determine the relationship between the perceived organizational support and work-life balance. The research method used was quantitative. The subjects of this study were 158 high school teachers with civil servant status in Samarinda with simple random sampling data collection techniques. The collection method used was the work-life balance scale and perceived organizational support. The data analysis technique used was the Pearson product moment correlation. The results of the validity test of the work-life balance scale and perceived organizational support obtained a value of r> 0.300 with all items declared valid. Based on the results of the study, it was found that there was a significant relationship between the perceived organizational support and work-life balance with r count 0.408> r table 0.131 and a sig value of 0.000 <0.05 which indicated a positive relationship. The higher the perceived organizational support, the higher the work-life balance of teachers. Therefore, schools and education stakeholders are expected to facilitate the psychological well-being of teachers by providing adequate support. With this support, it is hoped that teachers can carry out their duties better without sacrificing aspects of their personal lives, thus having a positive impact on the quality of education.Keseimbangan kehidupan kerja merupakan kemampuan membagi peran secara adil antara kehidupan pekerjaan dengan kehidupan pribadi. Salah satu faktor pendorong yang dapat meningkatkan keseimbagan kehidupan kerja yaitu faktor persepsi dukungan organisasi yang membuat guru merasakan kesejahteraan dalam menjalani kehidupan pekerjaan. Sehingga persepsi ini dibutuhkan untuk mencapai keseimbangan kehidupan kerja. Namun, kenyataannya masih ada guru yang kurang memiliki persepsi dukungan organisasi. Tujuan penelitian ini untuk mengetahui hubungan persepsi dukungan organisasi dengan keseimbangan kehidupan kerja. Metode penelitian yang digunakan yaitu kuantitatif. Subjek penelitian ini adalah 158 guru SMA sederajat berstatus PNS di Samarinda dengan teknik pengumpulan data simple random sampling. Metode pengumpulan yang digunakan adalah dengan skala keseimbangan kehidupan kerja dan persepsi dukungan organisasi. Teknik analisis data yang digunakan adalah korelasi pearson product moment. Hasil uji validitas skala keseimbangan kehidupan kerja dan persepsi dukungan organisasi didapatkan nilai r > 0.300 dengan seluruh aitem dinyatakan valid. Berdasarkan hasil penelitian ditemukan bahwa terdapat hubungan signifikan antara persepsi dukungan organisasi dan keseimbangan kehidupan kerja dengan r hitung 0.408 > r tabel 0.131 dan nilai sig 0.000 < 0.05 yang menunjukkan hubungan ke arah positif. Semakin tinggi persepsi dukungan organisasi maka semakin tinggi pula keseimbangan kehidupan kerja pada guru. Oleh karena itu, sekolah dan pemangku pendidikan diharapkan dapat memfasilitasi kesejahteraan psikologis guru dengan memberikan dukungan yang memadai. Dengan adanya dukungan tersebut, diharapkan para guru dapat menjalankan tugas mereka dengan lebih baik tanpa mengorbankan aspek kehidupan pribadi, sehingga berdampak positif pada kualitas pendidikan.